2018
DOI: 10.1097/dss.0000000000001537
|View full text |Cite
|
Sign up to set email alerts
|

Patients' Body Image Improves After Mohs Micrographic Surgery for Nonmelanoma Head and Neck Skin Cancer

Abstract: Patients' BI improves after treatment with MMS for NMHNSC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 17 publications
0
11
1
Order By: Relevance
“…Patients in our study who received reconstruction reported dissatisfaction with body appearance. This finding is dissimilar to that of a previous body image study . Patients with skin cancer of the head and neck who received microsurgery had better body image at 6 months after treatment.…”
Section: Discussioncontrasting
confidence: 99%
“…Patients in our study who received reconstruction reported dissatisfaction with body appearance. This finding is dissimilar to that of a previous body image study . Patients with skin cancer of the head and neck who received microsurgery had better body image at 6 months after treatment.…”
Section: Discussioncontrasting
confidence: 99%
“…[16][17][18][19] Because BID is a critical psychosocial issue for patients with HNC, there has been a proliferation of studies addressing the topic in recent years. [20][21][22][23][24][25][26] These studies have contributed to an improved conceptual framework for understanding BID in patients with HNC, reported on the changes in the severity of BID over time, described risk factors for BID, and characterized different treatment strategies. However, the volume of recent studies, differences in study design, varied patient populations, and heterogeneity of BID assessment tools have made understanding BID in patients with HNC challenging.…”
mentioning
confidence: 99%
“…Because BID is a critical psychosocial issue for patients with HNC, there has been a proliferation of studies addressing the topic in recent years 20‐26 . These studies have contributed to an improved conceptual framework for understanding BID in patients with HNC, reported on the changes in the severity of BID over time, described risk factors for BID, and characterized different treatment strategies.…”
mentioning
confidence: 99%
“…Our conceptual model of BID for patients with HNC is shown in Figure 1 . This model is informed by a model from Rhoten et al 10 and synthesizes our new qualitative findings about key themes and experiential modifiers of HNC-related BID with previously published risk factors for BID 35-39 and its negative outcomes. 2,28,40,41…”
Section: Resultsmentioning
confidence: 99%
“…(Participant 4) Social support ''I have a big support system, especially our church family so that helps a lot too.'' (Participant from Rhoten et al 10 and synthesizes our new qualitative findings about key themes and experiential modifiers of HNC-related BID with previously published risk factors for BID [35][36][37][38][39] and its negative outcomes. 2,28,40,41 Discussion Experiential Themes of BID…”
Section: Theme Examplesmentioning
confidence: 99%